1997
DOI: 10.1111/j.1651-2227.1997.tb14857.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and associated factors of epilepsy in children in Calicut District, Kerala, India

Abstract: To determine the prevalence of epilepsy and its association with indices of malnutrition, infection and perinatal complications in children in Calicut District, Kerala, India, a door-to-door two-stage survey was conducted in two local government districts. Among the random sample of 1172 children aged 8-12 y, 26 conformed to the definition of epilepsy giving a 5-y period prevalence of 22.2/1000. A history of perinatal complications, low BMI and recent physical symptoms were independently associated with active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
2
27
1
2
Order By: Relevance
“…For example, in India the treatment gap ranged from 40 to 90% in rural areas and from 22 to 50% in mixed, suburban and urban populations. 18,21,24,25 Similar trends were observed in Brazil, China, Pakistan and Togo. However, there were a few exceptions: in a rural population from Rajasthan, India, the treatment gap was 40% (the third lowest in India), 25 while in a rural population of Mali it was 65% (versus 76% in an urban population).…”
Section: Lower Middle Incomesupporting
confidence: 64%
“…For example, in India the treatment gap ranged from 40 to 90% in rural areas and from 22 to 50% in mixed, suburban and urban populations. 18,21,24,25 Similar trends were observed in Brazil, China, Pakistan and Togo. However, there were a few exceptions: in a rural population from Rajasthan, India, the treatment gap was 40% (the third lowest in India), 25 while in a rural population of Mali it was 65% (versus 76% in an urban population).…”
Section: Lower Middle Incomesupporting
confidence: 64%
“…In a Chinese study,[15] perinatal factors were the most frequently found cause of epilepsy. A population-based survey in a Northern district of Kerala state[16] showed that a history of perinatal complications, low body mass index, and recent physical symptoms were independently associated with active epilepsy in children of 8–12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the prevalence of active epilepsy (five-year period) among children from 0 to 14 years is low, comparable to the prevalence found by Hauser et al 2 in the city of Rochester in the USA and Kurtz et al 30 in Britain. In general, the recent epidemiological studies have pointed to a low rate in this age group, except for a study in India 31 in which the prevalence was high, probably due to malnutrition, perinatal problems and infections.…”
Section: Discussionmentioning
confidence: 99%